Angiotensin II Type 1 Receptor‐Associated Protein Regulates Kidney Aging and Lifespan Independent of Angiotensin. Issue 8 (August 2017) - Uneda, Kazushi; Wakui, Hiromichi; Maeda, Akinobu; Azushima, Kengo; Kobayashi, Ryu; Haku, Sona; Ohki, Kohji; Haruhara, Kotaro; Kinguchi, Sho; Matsuda, Miyuki; Ohsawa, Masato; Minegishi, Shintaro; et al.
Abstract : Background: The kidney is easily affected by aging‐associated changes, including glomerulosclerosis, tubular atrophy, and interstitial fibrosis. Particularly, renal tubulointerstitial fibrosis is a final common pathway in most forms of progressive renal disease. Angiotensin II type 1 receptor (AT1R)‐associated protein (ATRAP), which was originally identified as a molecule that binds to AT1R, is highly expressed in the kidney. Previously, we have shown that ATRAP suppresses hyperactivation of AT1R signaling, but does not affect physiological AT1R signaling. Methods and Results: We hypothesized that ATRAP has a novel functional role in the physiological age‐degenerative process, independent of modulation of AT1R signaling. ATRAP‐knockout mice were used to study the functional involvement of ATRAP in the aging. ATRAP‐knockout mice exhibit a normal age‐associated appearance without any evident alterations in physiological parameters, including blood pressure and cardiovascular and metabolic phenotypes. However, in ATRAP‐knockout mice compared with wild‐type mice, the following takes place: (1) age‐associated renal function decline and tubulointerstitial fibrosis are more enhanced; (2) renal tubular mitochondrial abnormalities and subsequent increases in the production of reactive oxygen species are more advanced; and (3) life span is 18.4% shorter (median life span, 100.4 versus 123.1 weeks). As a key mechanism, age‐related pathological changes in the kidney of ATRAP‐knockout mice correlated with decreased expression of the prosurvival gene, Sirtuin1 . On the other hand, chronic angiotensin II infusion did not affect renal sirtuin1 expression in wild‐type mice. Conclusions: These results indicate that ATRAP plays an important role in inhibiting kidney aging, possibly through sirtuin1‐mediated mechanism independent of blocking AT1R signaling, and further protecting normal life span.